Tumor necrosis factor-α mediated inflammation versus apoptosis in age-related hearing loss - Wu, Ting; Zhou, Jiamin; Qiu, Jingjing; Song, Yuwan; Guo, Wentao; Cui, Limei; Song, Xicheng; Sun, Yan (Frontiers in Aging Neuroscience, 2022)
An almost universal phenomenon occurring during ageing is a state of chronic, low-grade, sterile inflammation. Inflammation is a crucial contributor to various age-related pathologies and natural processes in aging tissues. Tumor necrosis factor-α (TNF-α), a master regulator of the immune system, plays an important role in the propagation of inflammation. Recent research has found correlations between hearing loss and markers such as TNF-α. However, the intrinsic molecular mechanism by which TNF-α influences aging individuals' increased risk of hearing loss remains unclear. In this study, we found that TNF-α expression gradually increased with age in DBA/2J mice. We then used recombinant TNF-α to upregulate TNF-α levels in House Ear Institute-Organ of Corti 1 (HEI-OC1) cells and found that low concentrations of TNF-α could activate the nuclear factor kappa B (NF-κB) transcriptional response to mediate hair cell survival, while high concentrations of TNF-α could activate the Caspase-3 cascade to mediate hair cell apoptosis, which preliminarily confirmed that a TNF-α mediated signaling pathway plays an important role in the pathogenesis of age-related hearing loss.